FLASH pilot survey: detections of associated 21 cm H i absorption in GAMA galaxies at 0.42 < z < 1.00. Issue 2 (18th August 2022) - Su, Renzhi; Sadler, Elaine M; Allison, James R; Mahony, Elizabeth K; Moss, Vanessa A; Whiting, Matthew T; Yoon, Hyein; Aditya, J N H S; Bellstedt, Sabine; Robotham, Aaron S G; Garratt-Smithson, Lilian; Gu, Minfeng; et al.
ABSTRACT: We present the results of a search for associated 21 cm H i absorption at redshift 0.42 < z < 1.00 in radio-loud galaxies from three Galaxy And Mass Assembly (GAMA) survey fields. These observations were carried out as part of a pilot survey for the Australian SKA Pathfinder (ASKAP) First Large Absorption Survey in H i (FLASH). From a sample of 326 radio sources with 855.5 MHz peak flux density above 10 mJy, we detected two associated H i absorption systems, in SDSS J090331+010847 at z = 0.522 and SDSS J113622+004852 at z = 0.563. Both galaxies are massive (stellar mass 10^11 M_ ) and have optical spectra characteristic of luminous red galaxies, though spectral energy distribution fitting implies that SDSS J113622+004852 contains a dust-obscured starburst with star formation rate ∼69 M⊙ yr −1 . The H i absorption lines have a high optical depth, with τpk of 1.77 ± 0.16 for SDSS J090331+010847 (the highest value for any z > 0.1 associated system found to date) and 0.14 ± 0.01 for SDSS J113622+004852. In the redshift range probed by our ASKAP observations, the detection rate for associated H i absorption lines (with τpk > 0.1 and at least 3σ significance) is 2.9_-2.6^+9.7 per cent. Although the current sample is small, this rate is consistent with a trend seen in other studies for a lower detection rate of associated 21 cm H i absorption systems at higher redshift. We also searched for OH absorption lines at 0.67 < z < 1.34, but no detection was made in the 145 radio sources searched.